(untitled) (Shanti Journal, 2023)
This study examines the impact of non-performing assets and profitability of commercial banks in Nepal. Out of 27 commercial banks, five joint venture banks have been selected as sample based on descriptive and analytical technique. Secondary data was collected from the annual reports of five selected commercial banks for the period of 2011/12 to 2020/21. Data have been collected and analyzed by using mean, standard deviation, and correlation and regression analysis. The profitability in terms of return on assets (ROA), return on equity (ROE) and profitability are selected as dependent variables. Non-performing assets (NPA), capital adequacy ratio (CAR) and total loan to total deposit ratio (TLTD) are taken as independent variables. The finding indicates that NPA has significant impact on the profitability of Nepalese joint venture banks. The result shows that ROE has been found a positive impact on the NPA, CAR and TLTD. Thus, this study concludes that non-performing assets is an important predictor for the profitability of the bank. Therefore, the success of the bank in term of profitability depends on its non-performing assets.